FINANCIAL EDUCATION ON THE BENEFITS AND RISKS OF USING FINTECH FOR GENERATION Z AT INSTIKI - I Dewa Ayu Agung Tantri Pramawati; Kompiang Martina Dinata Putri; I Putu Arya Mulyawan (Jurnal Scientia, 2023)
This research was conducted to provide literacy education to Generation Z, namely students about the benefits and risks, as well as how to be wise in using financial technology or FinTech. This literacy education is a very important enrichment for students amid the rapid innovations that occur in the trend of digital financial transactions and have not been widely elaborated in the campus curriculum. Studying this phenomenon, students must be introduced more closely to the benefits and risks of using financial technology or Fintech through the learning video "FinTech Digital Financial Innovation Trends". This data collection technique was carried out using observation, documentation and interview methods. Verification of data validity, in this study using data triangulation (data triangulation) and researcher triangulation (investigator triangulation). With the object of research is students who are studying at INSTIKI. This research aims to make Generation Z at the student level can increase understanding of FinTech products well. With this increased understanding, students are more aware of financial technology and are expected to be careful in its use in order to avoid fraud and theft of personal identity data.